Asuhan Keperawatan Pada An.G Dengan Gangguan Sistem Pencernaan: Gastroenteritis Akut (GEA) Di Ruang Anggrek I RSUD dr. Soeselo Kabupaten Tegal - Eli Suhesti; Esti Nur Janah; Ahmad Zakiudin (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Gastrointestinal disorders are quite dangerous diseases and cause number 6 deaths in the world. Based on data from the World Health Organization (WHO) in 2018, digestive tract diseases mostly occur in developing countries, looking at the prevalence of digestive tract disorders which are often experienced by everyone, such as diarrhea, hemorrhoids and anal fissures, both toddlers and adults are more susceptible to disease. in the digestive tract (Putra & Ary, 2021). Acute gastroenteritis is an infectious disease and is a global public health problem in developed and developing countries resulting in substantial morbidity and mortality (Lakhan et al., 2023).